America's first Olympics the St. Louis games of 1904 - Matthews, George R. (Univ. of Missouri Press, 2005)
"Explores the history of the 1904 Olympics, held in St. Louis, Missouri, which featured first-time African American Olympians, a controversial marathon, and documentation by photojournalist Jessie Tarbox Beals. Examines the controversy surrounding the transfer of the games from Chicago to St. Louis"--Provided by publisher.
Includes bibliographical references (p. 223-229) and index
Keywords: Olympic Games -- (3rd -- 1904 -- Saint Louis, Mo.); Olympische Spiele -- 3 -- 1904 -- Saint Louis, Mo.